2013
DOI: 10.1016/j.euromechflu.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced collapse of a bubble inside a deformable vessel

Abstract: Shockwave lithotripsy repeatedly focuses shockwaves on kidney stones to induce their fracture, partially through cavitation erosion. A typical side effect of the procedure is hemorrhage, which is potentially the result of the growth and collapse of bubbles inside blood vessels. To identify the mechanisms by which shock-induced collapse could lead to the onset of injury, we study an idealized problem involving a preexisting bubble in a deformable vessel. We utilize a high-order accurate, shock- and interface-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…When MBs collapse, they can create shockwaves, increasing the local pressure by 100 atm and the local temperature by several thousands of degrees (41). Shockwaves can cause substantial cell damage and possible cell lysis nearby (42). The destruction of MBs may cause high-energy microstreams or microjets that will result in shear stress on the membrane of an endothelial cell and increase its permeability (43).…”
Section: Discussionmentioning
confidence: 99%
“…When MBs collapse, they can create shockwaves, increasing the local pressure by 100 atm and the local temperature by several thousands of degrees (41). Shockwaves can cause substantial cell damage and possible cell lysis nearby (42). The destruction of MBs may cause high-energy microstreams or microjets that will result in shear stress on the membrane of an endothelial cell and increase its permeability (43).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that microbubbles could induce significant bioeffects on confining vasculature (15)(16)(17). The bioeffects range from increasing the vascular permeability for the chemotherapy drug and target gene delivery by opening the blood-brain barrier locally and transiently, to vessel rupture and occlusion (11,12,(18)(19)(20)(21)(22)(23).…”
Section: A B C Discussionmentioning
confidence: 99%
“…The numerical method, which is both shock and interface capturing, is based on the work on Johnsen & Colonius (2006). Since its development, MFC has been used to study non-spherical bubble collapse (Johnsen 2007;Johnsen & Colonius 2009) and shock-induced collapse of bubbles inside deformable vessels (Coralic & Colonius 2013). Verification of the algorithm via benchmark test cases and parallel performance metrics have previously been documented (Coralic & Colonius 2014;Coralic 2015;Meng 2016), and are not reproduced here.…”
Section: Methodsmentioning
confidence: 99%